A randomized multicenter study on ambulatory blood pressure and arterial stiffness in patients treated with valsartan/amlodipine or nifedipine GITS - Xu, Shao‐Kun (J Clin Hypertens (Greenwich), 2018)
In a pre‐specified subgroup analysis of a 12‐week randomized multicenter study, we investigated effects of valsartan/amlodipine 80/5 mg single‐pill combination (n = 75) and nifedipine GITS 30 mg (n = 75) on ambulatory blood pressure (BP) and arterial stiffness assessed by brachial‐ankle pulse wave velocity (PWV) in patients with uncontrolled hypertension. At week 12, the between‐treatment mean differences in systolic/diastolic BP were smaller for 24‐hour and daytime (–2.1/–1.7 and −2.0/−1.5 mm Hg, respectively, P ≥ 0.22) but greater (P < 0.01) for nighttime (–4.0/‐2.8 mm Hg, P ≤ 0.09), especially in sustained uncontrolled hypertension (−5.0/−4.1 mm Hg, P ≤ 0.04) and non‐dippers (−6.5/−3.7 mm Hg, P ≤ 0.07), in favor of valsartan/amlodipine. At week 12, PWV was significantly reduced from baseline by valsartan/amlodipine (n = 59, P < 0.0001) but not nifedipine (n = 59, P = 0.06). The changes in PWV were significantly associated with that in ambulatory systolic BP and pulse pressure in the nifedipine (P ≤ 0.0008) but not valsartan/amlodipine group (P ≥ 0.57), with a significant interaction (P ≤ 0.045). The valsartan/amlodipine combination was more efficacious than nifedipine GITS in lowering nighttime BP in sustained uncontrolled hypertension and non‐dippers, and in lowering arterial stiffness independent of BP lowering.